Direct and indirect evidence that productivity of Snowy Plovers Charadrius nivosus varies with occurrence of a nest predator - Burrell, Noah S; Colwell, Mark A (Wildfowl, 2012)
The Snowy Plover Charadrius nivosus is a threatened species of shorebird that breeds along the Pacific coast of North America where predation of eggs and chicks is thought to be a principal cause of low productivity and small population size. Data were collated over nine years (2001â€“2009) at 19 breeding locations in northern California to evaluate relationships between the activity of the main predator (Common Raven Corvus corax) suspected to compromise plover reproductive success and per capita fledging success of plovers, including video camera evidence. An index of raven activity correlated negatively with plover productivity and appeared in the five most-competitive models, accounting for 88% of corrected-Akaike weights explaining variation in per capita fledging success. Activity of humans and American Crows Corvus brachyrhynchos was weakly correlated with plover reproductive success. Video cameras (deployed in the last two years of the study at the site where corvid activity was highest and most plovers bred) showed that ravens caused 70% of nest failures at an average of 12 (Â± 2.82 s.e.) days after clutch initiation; humans (20%) or drifting sand/tidal overwash (10%) caused remaining losses. Video recordings suggested that the departure of an incubating plover prompted raven predation of eggs. These results substantiate the notion that the Common Raven is an important factor limiting plover productivity in northern California, which emphasises the need for more effective management measures for predators.